2016
DOI: 10.1038/jes.2016.74
|View full text |Cite
|
Sign up to set email alerts
|

Maternal/fetal metabolomes appear to mediate the impact of arsenic exposure on birth weight: A pilot study

Abstract: Arsenic exposure has been associated with low birth weight. However, the underlying mechanisms are not well understood. Alterations to metabolites may act as causal mediators of the effect of arsenic exposure on low birth weight. This pilot study aimed to explore the role of metabolites in mediating the association of arsenic exposure on infant birth weight. Study samples were selected from a well-established prospectively enrolled cohort in Bangladesh comprising 35 newborns and a subset of 20 matched mothers.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 38 publications
(48 reference statements)
0
12
0
Order By: Relevance
“…A pilot study reported that inorganic arsenic levels in toenails of pregnant women in the first trimester were correlated with that in umbilical cord serum, and the levels of butylglycine and tartrate in maternal peripheral blood were correlated with the low levels of inorganic arsenic in umbilical cord serum, but not with the levels of inorganic arsenic in prenatal toenails (Wei et al, 2017).…”
Section: Effects Of Arsenic Exposure On the Maternal Serum Metabolomic Profilementioning
confidence: 99%
See 1 more Smart Citation
“…A pilot study reported that inorganic arsenic levels in toenails of pregnant women in the first trimester were correlated with that in umbilical cord serum, and the levels of butylglycine and tartrate in maternal peripheral blood were correlated with the low levels of inorganic arsenic in umbilical cord serum, but not with the levels of inorganic arsenic in prenatal toenails (Wei et al, 2017).…”
Section: Effects Of Arsenic Exposure On the Maternal Serum Metabolomic Profilementioning
confidence: 99%
“…These studies measured the metabolomic profile in different biological samples, including maternal urine samples (n = 7), maternal plasma/serum samples (n = 7), cord plasma/serum samples (n = 5), and amniotic fluid (n = 1). These studies were conducted in eleven different countries, including France (n = 1) (Bonvallot et al, 2013), Portugal (n = 1) (Gil et al, 2018), Spain (n = 1) (Maitre et al, 2018), Poland (n = 1) (Zbucka-Kretowska et al, 2018), Germany (n = 1) (Rolle-Kampczyk et al, 2016), Belgium (n = 1) (Wei et al, 2017), USA (n = 3) (Fischer et al, 2017;Yan et al, 2019;Zhou et al, 2018), China (n = 3) Li et al, 2019;Wang et al, 2018a), Bangladesh (n = 1) (Wei et al, 2017), Japan (n = 1) (Eguchi et al, 2017), and Mexico (n = 1) (Laine et al, 2017). Three Chinese studies were conducted on the same population from the Wuhan Medical and Health Center for Women and Children.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…51 In the same cohort, iAs exposure was examined in intrauterine and maternal peripheral blood metabolites, and they were both found to influence the association between iAs toxicity and low birth weight. 52 Two pathways were identified from the mediation analysis between cord blood arsenic, metabolites, and birthweight, namely medium-chain fatty acid, and fatty acid, branched benzoate metabolism. 52 In summary, these studies support the relationship between altered gene DNA methylation and disease outcomes with iAs exposure.…”
Section: Ias-nutrition-dna Methylation Relationships In Humansmentioning
confidence: 99%
“…Prenatal As exposure has also been studied for associations with fetal metabolomics and proteomics. Prenatal exposure to inorganic arsenic (iAs) has been associated with variations in the cord serum metabolome, potentially related to regulation of the citrate cycle, as well as vitamin and amino acid metabolism [61], and a pilot study implicated that the toxic effects of in-utero iAs on birth weight may be mediated through alterations to metabolic activity in cord blood, specifically laurate, 17-methylstearate, and 4-vinylphenol sulfate [62]. Additionally, prenatal iAs has been associated with the expression of numerous proteins that are involved in Tumor necrosis factor (TNF) mediated immune and/or inflammatory response [63].…”
Section: Highlights Of -Omics Studies Of Prenatal Exposures and Earlymentioning
confidence: 99%